Monolayer tungsten disulfide in photonic environment : angle-resolved weak and strong light-matter coupling - Zhang, Xuewen (2022)
Light-matter interactions in two-dimensional transition metal dichalcogenides (TMDs) are sensitive to the surrounding dielectric environment. Depending on the interacting strength, weak and strong exciton-photon coupling effects can occur when the exciton energy is resonant with the one of photon. Here we report angle-resolved spectroscopic signatures of monolayer tungsten disulfide (1L-WS2) in weak and strong exciton-photon coupling environments. Inherent optical response of 1L-WS2 in the momentum space is uncovered by employing a dielectric mirror as substrate, where the energy dispersion is angle-independent while the amplitudes increase at high detection angles. When 1L-WS2 sits on top of a dielectric layer on silicon, the resonant trapped photon weakly couples with the exciton, in which the minimum of reflection dip shifts at both sides of the crossing angle while the emitted exciton energy remains unchanged. The unusual shift of reflection dip is attributed to the presence of Fano resonance under white-light illumination. By embedding 1L-WS2 into a dielectric microcavity, strong exciton-photon coupling results in the formation of lower and upper polariton branches with an appreciable Rabi splitting of 34 meV at room temperature, where the observed blueshift of the lower polariton branch is indicative of the enhanced polariton-polariton scattering. Our findings highlight the effect of dielectric environment on angle-resolved optical response of exciton-photon interactions in a two-dimensional semiconductor, which is helpful to develop practical TMD-based architectures for photonic and polaritonic applications. [Figure not available: see fulltext.]